The Urgency of Ummi Method Tahsin Teachers to Improve the Quality of Al-Qur'an Reading for Students - Erliani, Salsabila; Aulia, Icha Natasya; Jannah, Zahra; Kholilah Tanjung, Wardah; Akmalia, Rizki (LPPPIPublishing, 2024)
This research discusses the Urgency of Ummi Method Tahsin Teachers in Improving the Quality of Al-Qur'an Reading for Students. The Ummi method is a method of memorizing the Al-Qur'an quickly and accurately in recitation. The Ummi method is an approach developed to facilitate the process of learning the Al-Qur'an. This method is designed by considering students' basic abilities and placing emphasis on correct pronunciation in accordance with tajwid rules. The role of the tahsin teacher is very crucial in implementing the Ummi method. The method used in this research is a qualitative method, by interviewing relevant sources and also making observations at the destination. And the results obtained from this research are that tahsin teachers using the Ummi Method have great urgency in improving the quality of students' reading of the Al-Qur'an. This method helps students understand and master the rules of recitation in a systematic and easily accepted way. Although there are several challenges, such as time constraints and variations in student abilities. Therefore, the presence of trained and competent tahsin teachers is very important in efforts to improve the quality of Al-Qur'an reading among students.